Effects of Intravenous Ketamine Infusions in a Neuropathic Pain Patient with Lichen Sclerosus et Atrophicus - Ashraf F. Hanna (Case Reports in Dermatology, 2016)
A patient reported to the Florida Spine Institute (Clearwater, Fla., USA) with severe lichen sclerosus of the anogenital region and legs. The patient’s pain presentation was neuropathic with hypersensitivity, allodynia, swelling, and weakness. The patient had failed multiple pain management modalities including opioid therapy, anticonvulsants, and antidepressants. The patient completed a standard intravenous ketamine infusion regimen developed at the Florida Spine Institute and reported complete abolishment of her pain syndrome. For the first time, we report that ketamine infusions also dramatically improved a patient’s lichen sclerosus. That ketamine is known to have immunomodulatory properties, and given the clinical observations described in this case report, suggests that ketamine should be explored as a possible new therapeutic option for managing lichen sclerosus, especially in cases that are refractory to conventional therapies.